Quantum phonon transport in nanomaterials: Combining atomistic with non-equilibrium green's function techniques - Sandonas, Leonardo Medrano; Gutierrez, Rafael; Pecchia, Alessandro; Croy, Alexander; Cuniberti, Gianaurelio (Giovanni) (Entropy, 2019)
A crucial goal for increasing thermal energy harvesting will be to progress towards atomistic design strategies for smart nanodevices and nanomaterials. This requires the combination of computationally efficient atomisticmethodologies with quantum transport based approaches. Here, we review our recent work on this problem, by presenting selected applications of the PHONON tool to the description of phonon transport in nanostructured materials. The PHONON tool is a module developed as part of the Density-Functional Tight-Binding (DFTB) software platform. We discuss the anisotropic phonon band structure of selected puckered two-dimensional materials, helical and horizontal doping effects in the phonon thermal conductivity of boron nitride-carbon heteronanotubes, phonon filtering in molecular junctions, and a novel computational methodology to investigate time-dependent phonon transport at the atomistic level. These examples illustrate the versatility of our implementation of phonon transport in combination with density functional-based methods to address specific nanoscale functionalities, thus potentially allowing for designing novel thermal devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Density-functional tight binding; Green's functions; Landauer approach; Nanostructured materials; Phonon transport; Time-dependent transport